2001
DOI: 10.4049/jimmunol.166.2.1066
|View full text |Cite
|
Sign up to set email alerts
|

Lymphotoxin α−/− Mice Develop Functionally Impaired CD8+ T Cell Responses and Fail to Contain Virus Infection of the Central Nervous System

Abstract: Recent observations have indicated that viral persistence and tumor spreading could occur because of effector function-defective CD8+ T cells. Although chronic exposure to Ag, lack of CD4 help, and epitope dominance are suggested to interfere with CTL differentiation, mechanisms underlying the defective effector function remain obscure. We demonstrate in this report that lymphotoxin α-deficient mice develop CD8+ T cells at normal frequencies when infected with HSV or immunized with OVA Ag but show impaired cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
47
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 34 publications
1
47
1
Order By: Relevance
“…1). Recent reports describing an association between disruption of mlT and defects in host immunity have linked this effect to impaired function of CD8 ϩ T cells (15,17). Thus, we hypothesized that the rejection observed in LT␣ Ϫ/Ϫ mice was mediated by CD4 ϩ T cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Recent reports describing an association between disruption of mlT and defects in host immunity have linked this effect to impaired function of CD8 ϩ T cells (15,17). Thus, we hypothesized that the rejection observed in LT␣ Ϫ/Ϫ mice was mediated by CD4 ϩ T cells.…”
Section: Resultsmentioning
confidence: 99%
“…The binding of mlT expressed by T cells and activated B cells to lymphotoxin ␤ receptor (LT␤R) expressed on stromal cells and cells of monocytic origin has been shown to be critical for the development of lymphoid organs (13) and for the regulation of chemokine production (14). Disruption of these molecular interactions has been reported to impair the immune response to viruses and tumors (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…This result reinforces the conclusion that TNF-mediated protection against HSV-1-induced mortality is independent of signaling via the known TNF receptors, p55 and p75. Although the monomeric sTNFR1 preparation used does not bind LT when tested in vitro, there is a remote possibility that in vivo it might bind LT in addition to TNF, both of which are natural ligands for p55 that have been implicated in the mediation of resistance to HSV-1 (8,24,39). Consequently, we also tested an anti-TNF monoclonal antibody (MAb) that does not bind LT and demonstrated that mortality due to HSE was increased to an extent similar to that observed with sTNFR1 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The CTL assay was performed as described earlier (21). Briefly, effector cells generated after in vitro expansion (with peptide or HSV) were analyzed for their ability to kill MHC-matched Ag-presenting targets.…”
Section: Ctl Assaysmentioning
confidence: 99%
“…The targets included 51 Cr-pulsed, MHC-matched, and HSV-infected (EMT6-HSV), MHC-matched and DYATLGVGV-pulsed (EMT6-DYATL GVGV), MHC-mismatched, HSV-infected, and DYATLGVGV-pulsed (MC38-HSV and MC38-DYATLGVGV), and MHC-matched uninfected or unpulsed (EMT6) targets. The chromium release results were computed and are expressed as lytic units as described elsewhere (21).…”
Section: Ctl Assaysmentioning
confidence: 99%